Luther [videorecording (DVD)] : his life, his path, his legacy. (NFP teleart GmbH & Co. ; FilmTel, Inc., 2014)
Vary few historical figures have affected modern society and humanity as enduringly as Martin Luther, and on such a global scale. This comprehensive documentary traces the footsteps of the great Reformer and reflects upon the places which have become inseparably connected with his name.